PILIHAN SISTEM MANAJEMEN PERSONIL PEMERINTAH DAERAH - Irfan Ridwan Maksum (Badan Kepegawaian Negara | The National Civil Service Agency, 2007)
Local government personnel management in Indonesia has not been changed fundamentally whether structural or cultural since reform induced at the end of 1990s. Under law Number 22 of 1999, based on articles 7 and 75 the local personnel system moving forward to separete system. But, the local government is not capable to carry-out this system running well. Finally, under law number 32 of 2004, it still being sentralized with ’pangreh-praja’ culture. Keyword: management, personnel system, local government.